Validity And Reliability Of Connor-Davidson Resilience Scale (CD-RISC) 10 Items On Pregnant Women - Perwitasari; Risky Puji Wulandari (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Background: Pregnancy period trigger emotional challenges for women, not only due to hormonal changes but also due to physical, psychological, social, financial and cultural factors. Women’s reaction to stress or difficult conditions is considered as resilience. Pregnant women who have low levels of resilience tend to report high perceptions of stress, so increasing resilience in pregnant women is important for building positive coping strategies to minimize the negative effects of stress on the mother and fetus. One of the tools that is often used to assess resilience is Connor-Davidson Resilience Scale (CD-RISC). This study aimed to test the validity and reliability of the 10-item CD-RISC on pregnant women sample. Method: This research was descriptive statistical to test the validity and reliability of the CD-RISC 10-items on 30 respondents in Magelang, Central Java. Result: The pearson correlation and cronbach alpha was used to assess validity and reliability. The statistical test results showed that the item correlation value for all items ranged from 0.711 to 0.906, r values from 10 items had score above the r table (0.361). The cronbach alpha value was 0.940. Discussion: Researchers assumed that apart from being valid and reliable, the resilience theory on the Connor-Davidson Resilience Scale (CD-RISC) shows relevance to culture and values adopted by pregnant women in Indonesia, therefore this tool can be employed to explore the level of resilience of pregnant women in quantitative or qualitative research. Conlussion: This study conclude that CD-RISC 10 items has good validity and reliability for assessing the resilience of pregnant women in Indonesia